Embedding Mabadi Khaira Ummah into internal control systems to strengthen governance and performance in Islamic cooperatives: A case study of KSPPS Nusa Umat Sejahtera Semarang - Hidayat, Solikhul; Wahidmurni, Wahidmurni; Wahyuni, Nanik (Universitas Islam Indonesia, 2026)
IntroductionIslamic cooperatives have become vital institutions for promoting inclusive finance and member-based economic development. However, their sustainability requires robust governance and reliable internal control systems. Few studies have examined how Islamic ethical values, particularly Mabadi Khaira Ummah, can be systematically embedded into internal control frameworks to enhance transparency, accountability, and organizational performance.ObjectivesThis study aims to analyze how Mabadi Khaira Ummah—truthfulness, trust, justice, cooperation, and steadfastness—are conceptualized, implemented, and operationalized in the internal control system of KSPPS Nusa Umat Sejahtera. It further explores the impact of these values on cooperative governance, fraud prevention, and financial performance.MethodA qualitative case study approach was employed, focusing on KSPPS Nusa Umat Sejahtera in Semarang, Indonesia. Data were collected through semi-structured interviews, direct observation, and document analysis. Purposive and snowball sampling were used to identify respondents, and thematic analysis was applied to examine how ethical values were integrated into organizational practices.ResultsThe findings reveal that Mabadi Khaira Ummah values are embedded into standard operating procedures, staff training, monitoring processes, and member engagement. Their application has enhanced transparency, strengthened accountability, reduced fraud risks, and supported asset growth. Members perceive the cooperative as both a financial institution and a moral community, reinforcing trust and loyalty.ImplicationsThis study provides theoretical, practical, and policy implications. It extends governance theory by demonstrating how ethical values reshape accountability as a moral duty. Practically, it offers a replicable model for other Islamic cooperatives. At the policy level, it highlights the need for regulatory frameworks that promote ethics-driven governance.Originality/NoveltyThe study contributes to the literature by empirically showing how Mabadi Khaira Ummah principles can be institutionalized within internal control systems, bridging the gap between normative Islamic ethics and operational governance in Sharia-based cooperatives.